The role of the didactic model of textual genres in language teaching - Abreu-Tardelli, Lília Santos [UNESP]; Apostolo, Malu Ciencia [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2018)
- This article aims at clarifying the concept of the didactic model of textual genres in the Sociodiscursive Interactionism’s perspective from the Genevan authors of the Didactic of Language, a fundamental concept (but still misunderstood) to the understanding of language teaching through textual genres, a proposal based on the Vy-gotskian theory of human development. Therefore, we will review this concept based on authors from the University of Geneva as well as on Brazilian authors who dedicate themselves to this theme.
O papel do modelo didático de gêneros textuais no ensino de línguas
Keywords: Didactic model of genres; Language capacities; Textual genres and language teaching